Pengujian Puntir Poros Komposit Serat Gelas Berlapis Simetri Dengan Lapisan Bersudut ( Angle Ply) Torsion Testing Of symetrical Anegel Ply Laminated Glass/ Epoxy Composite Shaft - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Glass/epoxy composite shafts were tested under torsion loading. The material which was made by filament winding method is simetric angle-ply laminate with 4 plies. The fiber orientations q, were varied from 15 degrees to 75 degrees to the tube axis, to make laminated composite with [q,-q]3structure. It was shown from the experimental result, that the shear strength of the shaft is agree better with Tsai-Hill failure criteria than with the maximum stress criteria. The shear stiffness, however, is below the calculated value.